Agonist anti-GITR monoclonal antibody and stereotactic radiation induce immune-mediated survival advantage in murine intracranial glioma. Issue 1 (17th May 2016) - Patel, Mira A.; Kim, Jennifer E.; Theodros, Debebe; Tam, Ada; Velarde, Esteban; Kochel, Christina M.; Francica, Brian; Nirschl, Thomas R.; Ghasemzadeh, Ali; Mathios, Dimitrios; Harris-Bookman, Sarah; Jackson, Christopher C.; et al.
Abstract : Background: Glioblastoma (GBM) is a poorly immunogenic neoplasm treated with focused radiation. Immunotherapy has demonstrated synergistic survival effects with stereotactic radiosurgery (SRS) in murine GBM. GITR is a co-stimulatory molecule expressed constitutively on regulatory T-cells and by effector T-cells upon activation. We tested the hypothesis that anti-GITR monoclonal antibody (mAb) and SRS together would confer an immune-mediated survival benefit in glioma using the orthotopic GL261 glioma model. Methods: Mice received SRS and anti-GITR 10 days after implantation. The anti-GITR mAbs tested were formatted as mouse IgG1 D265A (anti-GITR (1)) and IgG2a (anti-GITR (2a)) isotypes. Mice were randomized to four treatment groups: (1) control; (2) SRS; (3) anti-GITR; (4) anti-GITR/SRS. SRS was delivered to the tumor in one fraction, and mice were treated with mAb thrice. Mice were euthanized on day 21 to analyze the immunologic profile of tumor, spleen, and tumor draining lymph nodes. Results: Anti-GITR (1)/SRS significantly improved survival over either treatment alone ( p < .0001) with a cure rate of 24 % versus 0 % in a T-lymphocyte-dependent manner. There was elevated intratumoral CD4+ effector cell infiltration relative to Treg infiltration in mice treated with anti-GITR (1)/SRS, as well as significantly elevated IFNγ and IL-2 production by CD4+ T-cells and elevated IFNγ and TNFα production by CD8+ T-cells. There was increased mRNA expression of M1 markers and decreased expression of M2 markers in tumor infiltrating mononuclear cells. The anti-GITR (2a)/SRS combination did not improve survival, induce tumor regression, or result in Treg depletion. Conclusions: These findings provide preclinical evidence for the use of anti-GITR (1) non-depleting antibodies in combination with SRS in GBM.